Development of Relation and Function e-Modules Based on Contextual Learning Integrated with Islamic Values - Radjak, Dwi Setiawati; Turmudi, Turmudi; Sujarwo, Imam (Yayasan Nurul Yakin Bunga Tanjung, 2024)
This research aims to develop an e-module about relations and functions based on contextual learning that is integrated with Islamic values ​​that are valid, practical, and interesting. The research carried out is development research (R&D) using the ADDIE model, which goes through 5 stages, namely analysis, design, development, implementation, and evaluation. The research subjects were class VIII students at MTs Arafah Bitung, North Sulawesi. The data obtained was analyzed descriptively, and percentage data was used to represent the results. The research results show that the e-module developed on relation and function material is valid, practical, and interesting. The validity test obtained an average feasibility percentage of 86.8%. The practicality test obtained an average feasibility percentage of 90.1%. Meanwhile, the attractiveness test obtained an average feasibility percentage of 87.7%. The relations and function e-module specifications developed include understanding the concepts of relations and functions and presenting relations and functions based on integrated contextual learning of Islamic values. This proves that the e-module is suitable for use as teaching material and a means of independent education in the learning process.